Whole‐Cell P450 Biocatalysis Using Engineered Escherichia coli with Fine‐Tuned Heme Biosynthesis. Issue 6 (16th December 2022) - Hu, Baodong; Yu, Haibo; Zhou, Jingwen; Li, Jianghua; Chen, Jian; Du, Guocheng; Lee, Sang Yup; Zhao, Xinrui
Abstract: By exploiting versatile P450 enzymes, whole‐cell biocatalysis can be performed to synthesize valuable compounds in Escherichia coli . However, the insufficient supply of heme limits the whole‐cell P450 biocatalytic activity. Here a strategy for improving intracellular heme biosynthesis to enhance the catalytic efficiencies of P450s is reported. After comparing the effects of improving heme transport and biosynthesis on P450 activities, intracellular heme biosynthesis is optimized through the integrated expression of necessary synthetic genes at proper ratios and the assembly of rate‐limiting enzymes using DNA‐guided scaffolds. The intracellular heme level is fine‐tuned by the combined use of mutated heme‐sensitive biosensors and small regulatory RNA systems. The catalytic efficiencies of three different P450s, BM3, sca‐2, and CYP105D7, are enhanced through fine‐tuning heme biosynthesis for the synthesis of hydroquinone, pravastatin, and 7, 3′, 4′‐trihydroxyisoflavone as example products of chemical intermediate, drug, and natural product, respectively. This strategy of fine‐tuned heme biosynthesis will be generally useful for developing whole‐cell biocatalysts involving hemoproteins. Abstract : Here, the development of an engineered E. coli strain capable of improved heme supply suitable for whole‐cell P450 biocatalysts is reported. The intracellular heme level is fine‐tuned by the combined use of mutated heme‐sensitive biosensors and small regulatory RNA systems. This strategy of fine‐tuned heme biosynthesis will be generally useful for developing whole‐cell biocatalysts involving hemoproteins.